Beyond the racial state : rethinking Nazi Germany - Pendas, Devin O. HerausgeberIn; Roseman, Mark HerausgeberIn; Wetzell, Richard F. HerausgeberIn (Publications of the German Historical Institute, 2017)
Part I. Comparative and historical perspectives -- Racial discourse, Nazi violence, and the limits of the racial state model / Mark Roseman -- The murder of European Jewry : Nazi genocide in continental perspective / Donald Bloxham -- Meanings of race and biopolitics in historical perspective / Pascal Grosse -- Racial states in comparative perspective / Devin O. Pendas -- Part II. Race, science, and Nazi biopolitics -- Eugenics and racial science in Nazi Germany : was there a genesis of the "Final Solution" from the spirit of science? / Richard F. Wetzell -- Race science, race mysticism, and the racial state / Dan Stone -- Ideology's logic : the evolution of racial thought in Germany from the Volkisch movement to the Third Reich / Christian Geulen -- Nazi medical crimes, eugenics, and the limits of the racial state paradigm / Herwig Czech -- Part III. Anti-semitism beyond race -- "The axis around which national socialist ideology turns" : state bureaucracy, the Reich Ministry of the Interior and racial policy in the first years of the Third Reich / Jurgen Matthaus -- Neither Aryan nor Semite : reflections on the meanings of race in Nazi Germany / Richard Steigmann-Gall -- Racializing historiography : anti-Jewish scholarship in the Third Reich / Dirk Rupnow -- Part IV. Race and society -- Volksgemeinschaft : a controversy / Michael Wildt -- Mothers, whores, or sentimental dupes? : emotion and race in historiographical debates about women in the Third Reich / Annette F. Timm -- Nationalist mobilization : foreign diplomats' views on the Third Reich, 1933-1945 / Frank Bajohr -- Race and humor in Nazi Germany / Martina Kessel -- Legitimacy through war? / Nicholas Stargardt -- Part V. Race war? : Germans and non-Germans in wartime -- Negotiating Volkisch and racial identities : the Deutsche Volksliste in annexed Poland / Gerhard Wolf -- Sex, race, Volksgemeinschaft : German soldiers' sexual encounters with local women and men during the war and the occupation in the Soviet Union, 1941-1945 / Regina Muhlhauser -- The disintegration of the racial basis of the concentration camp system / Stefan Hordler